MONOGRAPH ASPECTS OF THE SINGLE GAME IN TENNIS - Teuşdea Claudiu Cristian (Universitaria Publishing House, Craiova, 2017)
In tennis the 5 samples, single game is the most popular and accessible for all ages. In the past, the single game was characterized by a small number of technical procedures, volume, intensity, complexity, small or medium effort, high velocity of the ball, rapid execution only in certain phases of point dispute and playing time. Single game play has evolved considerably in recent years due to the complete change in materials, equipment, gaming surfaces, technical skills, tactics, learning methodology, and the improvement of specific techniques.